Participac??o do sistema calicre??na-cininas na cardioprote????o promovida pela atividade f??sica e sua modula????o pela sobrecarga adren??rgica induzida pelo isoproterenol em mioc??rdio de ratos - Santana, Eduardo Tadeu (2011)
Exercise training exerts a cardioprotection, and the expression of local kallikrein-kinin system may contribute to this effect. To test this hypothesis in a model of ??-adrenergic hyperactivity, male Wistar rats were assigned into following four groups: sedentary non-treated (Con); sedentary isoproterenol-treated (Iso); exercised non-treated (Ex); and exercised plus isoproterenol (Iso+Ex). Isoproterenol increased cardial kinin B1 receptor gene expression (p<0.05). However, in the Iso+Ex group, where exercise training prevented LV hypertrophy and improved myocardial contractility, an increased expression of tissue kallikrein was observed (p<0.01). These data suggest the participation of the tissue kallikrein in a cardioprotective response of the myocardium towards ??-adrenergic hyperactivity.